P36 | BIOLOGICAL ROLE OF DNA G-QUADRUPLEX DURING LIVER REGENERATION AFTER PARTIAL HEPATECTOMY (European Journal of Histochemistry)
Guanine-rich DNA sequences can form four-stranded secondary structures known as G-quadruplexes (G4s). G4s exist in chromatin DNA and have linked G4 formation with the key processes from transcription and translation to genome instability1. However, the biological roles of G4s in vivo remain unclear. In this study, we investigated the localization in G4s during liver regeneration by immunohistochemistry in wild-type (WT) and a high-mobility group box 2 (HMGB2) knockout (KO) mice, where HMGB2, a chromatin associated protein, has been implicated as a G4 binding protein2,3. Liver tissues were sampled at 0, 24, 36, 48, 72, 120, 168 h after 70% partial hepatectomy (PHx). In WT mice, G4 positive cells were not detected at 0 hr after PHx, but were increased at 24 h and peaked at 36 h. Subsequently, G4 positive cells were gradually decreased. G4 positive cells were mainly localized in the nuclei of hepatocytes in the peripheral region between periportal (zone 1) and midzonal (zone 2) regions, but not in the pericentral (zone 3) region. To investigate the G4 formation during cell cycle progression, we evaluated the expression of cell cycle markers, including Cyclin D1, proliferating cell nuclear antigen (PCNA), 5ethynyl-2’-deoxyuridine (EdU), Cyclin A2 and phosphorylated H3S10 (pH3S10). G4 positive cells were colocalized with EdU and Cyclin A2 at 36 and 48 hr after PHx, but no colocalization with Cyclin D1, PCNA, or pH3S10. In HMGB2-KO mice, the number of G4 positive cells was significantly reduced compared with WT mice, although the temporal peak at 36 hr after PHx was preserved. In conclusion, DNA G4s may play a direct and crucial role in the liver regeneration after PHx for the cell cycle regulation, particularly with DNA synthesis.